Municipal wastewater phosphorus removal by coagulation - Yang, Kai (Environmental technology, 2010)
This study investigated the chemical removal of phosphorus from wastewater by means of adsorption and precipitation. Using secondary effluent from municipal wastewater treatment plants as the model wastewater, phosphorus precipitation was tested with four commonly used metal salt coagulants, and phosphorus adsorption was explored by column experiments with goethite-coated silica sand as porous media. It was concluded that adsorption played a more important role than precipitation in phosphorus removal. As demonstrated by the column experiments (integration of the breakthrough curve), around 65% of phosphorus can be retained through adsorption by goethite-coated silica sand